(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2024)
This paper explores hate speech issues through the lens of human rights and social justice, focusing particularly on its impact on minority communities in Pakistan. It examines how hate speech undermines their human rights and leads to a denial of social justice, eroding the social fabric and perpetuating discrimination. The paper begins with a discussion of the current global context and then delves into the socio-political landscape of Pakistan, presenting relevant background information. It highlights that Pakistan, marked by religious, cultural, ethnic, and linguistic diversity, has struggled to fully embrace this diversity. Within this context, the article specifically studies the issue of online hate speech directed at minority communities and its detrimental effects on their well-being and societal integration. The paper concludes with comprehensive recommendations to tackle hate speech both online and offline, aiming to promote a more inclusive and just society for all, where every individual’s rights are respected and protected.